Copper red glaze and red jade tiles fired in an oxidizing atmosphere

By using a combination of low-temperature protective glaze, copper-aluminum alloy particles and protective copper alloy particles, the copper-red glaze is fired in an oxidative atmosphere, which solves the problems of traditional firing difficulty and harsh conditions, and achieves bright colors and improved yield Effect.

CN116395960BActive Publication Date: 2025-02-14FOSHAN DOWSTONG TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310188478.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-28
Publication Date
2025-02-14
Estimated Expiration
2043-02-28

AI Technical Summary

Technical Problem

The existing copper red glaze is difficult to fire, and requires a specific reducing flame atmosphere, which leads to harsh firing conditions and difficult to industrialize, and limits its decorative effect.

Method used

The combination of low-temperature protective glaze, copper-aluminum alloy particles and protective copper alloy particles is adopted to fire copper-red glaze in an oxidative atmosphere through specific chemical composition and process flow, expanding the adaptation range of firing conditions.

Benefits of technology

It has achieved the copper-red glaze under conventional firing conditions (non-reducing atmosphere), with bright colors and significantly improved yield, breaking the traditional limitations of the need for a reduction atmosphere.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116395960B_ABST
    Figure CN116395960B_ABST
Patent Text Reader

Abstract

The present invention discloses copper red glaze and Zhonglang red jade tile fired in an oxidizing atmosphere, a copper red glaze with wide firing conditions, composed of low-temperature protective glaze, copper-aluminum alloy particles, and protective copper alloy particles, wherein the protective copper alloy is a copper alloy other than copper-aluminum alloy, wherein the initial melting temperature of the low-temperature protective glaze does not exceed 1050°C, and its raw materials mainly include feldspar, quartz, calcite, calcined kaolin, barium carbonate, zinc oxide, potassium nitrate, and potassium carbonate. The copper red glaze of the present invention effectively protects the copper-aluminum alloy particles by using a low-temperature protective glaze and a protective copper alloy of a specific composition, so that ceramic tiles can be fired under conventional firing conditions (non-reducing atmosphere) with bright colors, breaking the limitation that a reducing atmosphere is generally required to obtain copper red glaze in the prior art. At the same time, the copper red glaze of the present invention can be fired under relatively wide conditions, and the yield rate is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ceramics, and in particular relates to copper red glaze and Zhonglang red jade-fat ceramic tiles fired in an oxidizing atmosphere. Background Art

[0002] Copper red glaze is a red glaze made by using copper-containing substances as colorants and firing in a reducing flame. Theoretically, using copper oxide as a colorant and firing in a reducing flame can produce a bright red color.

[0003] Copper red glaze originated in the Tang Dynasty. In the late Yuan Dynasty and early Ming Dynasty, Jingdezhen began to produce red glaze wares. The bright red (also known as "Jihong" and "Jihong") of Yongle and Xuande in the early Ming Dynasty was the most famous. During firing, the kiln where the copper red glaze product is placed, the temperature and atmosphere in the kiln, and even the weather and seasonal changes outside the kiln, all have a great impact on its firing. With the traditional firing method, red glaze porcelain can be regarded as "one red in a thousand kilns", and it is said that nine out of ten kilns fail to produce red. Due to the great difficulty of firing copper red glaze, copper red glaze was once lost in the mid-Ming Dynasty, so alum red was fired instead. It was not until the Kangxi period of the Qing Dynasty that it was restored and fired into precious varieties such as Langyao Red and Cowpea Red.

[0004] The bright red copper red glaze is extremely rare and is treasured by the world. Traditional copper red glaze can only be fired in a proper reducing flame atmosphere to obtain a beautiful red color, but if the firing conditions are slightly off, the reduction is incomplete, or partial oxidation may cause the copper red effect to fail, or turn gray, green, black, or burn out.

[0005] Modern research shows that during the firing process, copper red glaze is greatly affected by external factors and internal conditions. It is affected by four aspects: kiln temperature, kiln atmosphere, glaze formula, colorant and reducing agent content. Zhao Qingnan et al. (Zhao Qingnan, Shi Zunchang. Study on the imitation and coloring mechanism of copper red glaze (I) [J]. Ceramic Science and Art, 1995, 029 (004): 3-6., Zhao Qingnan, Shi Zunchang. Study on the imitation and coloring mechanism of copper red glaze (II) [J]. Ceramic Engineering, 1995, 029 (005): 3-6.) pointed out that under the same firing conditions, when the CuO content is less than 1%, the glaze color almost does not change when the CuO content is increased or decreased. When the CuO content is greater than 1.6%, the glaze color deepens and darkens. The reducing atmosphere should be appropriate. Increasing the reducing atmosphere will make the glaze surface turn black, and light reducing atmosphere will make the glaze surface light green. Tan Xunyan et al. (Tan Xunyan. Trial production of a new copper red glaze [J]. Journal of Ceramics, 2012, 033(004): 496-499.) used kaolin, feldspar, quartz, limestone or calcite commonly used in the ceramic industry as the main raw materials for glaze making, adjusted the copper red glaze formula through the triangle batching method and the single factor test method, and trial-produced a new copper red glaze, and studied the effects of the basic glaze raw material ratio, glaze layer thickness and firing atmosphere on the glaze color. The results show that the appropriate amount of potassium feldspar in the basic glaze is 30wt.%, the amount of limestone is 20wt.%, and the amount of dolomite is 10wt.%; the glaze layer thickness is preferably 1.5-2mm; and the firing atmosphere is preferably a reducing flame.

[0006] Liu Xukuan et al. (Liu Xukuan, Du Banghong, Zhang Hongyin, et al. Copper red glaze fired by oxidizing flame [J]. Shandong Ceramics, 1994, 17 (3): 3.) used SiC as a reducing agent and adopted oxidizing flame firing to successfully trial-produce copper red glaze fired at 1250-1260°C, overcoming the shortcomings of the traditional reduction roasting method, simplifying the production process, and improving the yield of copper red glaze. In essence, it still uses SiC high temperature reaction to generate CO to convert the oxidizing atmosphere into a reducing atmosphere. This method has extremely stringent requirements on the firing conditions and is difficult to industrialize. CN106746655A also discloses a similar strategy.

[0007] CN104150965A discloses a copper red glaze formula and a glazing process thereof. The copper red glaze formula uses the following raw materials, and its composition is calculated by weight as follows: 40%-50% feldspar, 15%-25% quartz, 10%-15% limestone, 10%-15% grain ash, 1%-5% bone ash, 5%-10% tin, and 0.5%-1.5% copper. The porcelain made using the copper red glaze has a uniform color, a thick glaze, a white glaze, and a dark red color from the white glaze, which has a unique artistic effect and gives people a deep, stable, dignified and atmospheric look. Its red color is not bright enough and fails to show the copper red glaze.

[0008] Nowadays, copper red glaze is difficult to imitate in the field of daily-use porcelain. Its historical value, cultural value, economic value, artistic value, and collection value make people willing to spend a fortune on it. The firing atmosphere of traditional porcelain is generally an oxidizing atmosphere. The reducing atmosphere required by copper red glaze makes it difficult to use copper red glaze with other color glazes, which also limits its decorative effect to a certain extent.

[0009] How to reduce the difficulty of firing copper red glaze is of very practical significance. Summary of the invention

[0010] The object of the present invention is to overcome at least one disadvantage of the prior art and to provide a copper red glaze and Zhonglang red jade tile fired in an oxidizing atmosphere.

[0011] The technical solution adopted by the present invention is:

[0012] The first aspect of the present invention provides:

[0013] A copper red glaze with wide firing conditions is composed of low-temperature protective glaze, copper-aluminum alloy particles, and protective copper alloy particles. The protective copper alloy is a copper alloy other than copper-aluminum alloy. The initial melting temperature of the low-temperature protective glaze does not exceed 1050°C. The chemical mass composition of the low-temperature protective glaze is: Al2O3: 6.02-11.21%, SiO2: 55.22-65.15%, Fe2O3: 0-0.5%, CaO: 10-13.5%, MgO: 0-0.5%, K2O: 4-7%, Na2O: 1-3%, TiO2: 0-0.2%, ZrO2: 0-0.35%, BaO: 2-3.5%, ZnO: 6-13%, B2O3: 0-2% and unavoidable impurities.

[0014] In some examples of copper red glaze, the raw material mass composition of the low-temperature protective glaze is: feldspar: 30-40 parts, quartz: 18-30 parts, calcite: 10-25 parts, calcined kaolin: 5-10 parts, barium carbonate: 0-5 parts, zinc oxide: 5-15 parts, potassium nitrate: 0-5 parts, and potassium carbonate 1-6 parts.

[0015] In some examples of copper red glaze, the copper-aluminum alloy particles have at least one of the following characteristics:

[0016] 1) The amount of the copper-aluminum alloy particles is 0.2-20% of the dry weight of the low-temperature protective glaze;

[0017] 2) The copper content of the copper-aluminum alloy is 80-99%;

[0018] 3) The particle size of the copper-aluminum alloy particles is 100-500 meshes.

[0019] In some examples of copper red glaze, the protective copper alloy particles have at least one of the following characteristics:

[0020] 1) The protective copper alloy is selected from at least one of bronze powder, brass powder and copper-tungsten powder;

[0021] 2) The total copper content of the protective copper alloy is 85-99%;

[0022] 3) The amount of the protective copper alloy particles is 0.2-5% of the dry weight of the low-temperature protective glaze and is lower than the amount of the copper-aluminum alloy particles;

[0023] 4) The particle size of the protective copper alloy particles is 100 to 500 meshes.

[0024] In some examples of copper red glaze, the amount of the protective copper alloy particles is 0.2 to 0.5 times the amount of the copper-aluminum alloy particles.

[0025] The above features can be combined arbitrarily unless they conflict with each other.

[0026] The second aspect of the present invention provides:

[0027] A Zhonglang glaze red jade tile has a glaze layer formed by the copper red glaze described in the first aspect of the present invention.

[0028] In some examples of glazed Zhonglang red jade tiles, it includes a body layer, a base glaze layer, a copper red glaze layer and a polishing glaze layer.

[0029] In some examples of glazed Zhonglang red jade tiles, the thickness of the copper red glaze layer is 0.5-0.8 mm.

[0030] In some examples of glaze Zhonglang red jade tiles, the thickness of the glaze layer is 0.2-0.5 mm.

[0031] In some examples of glaze Zhonglang red jade tiles, the thickness of the copper red glaze layer is 0.5-0.8 mm, and the thickness of the polished glaze layer is 0.2-0.5 mm.

[0032] The third aspect of the present invention provides:

[0033] A method for preparing a copper-red glaze ceramic tile, wherein the composition of the copper-red glaze is as described in the first aspect of the present invention, comprising the following steps:

[0034] S1) preparing materials according to the composition of copper red glaze raw materials and mixing the raw materials uniformly;

[0035] S2) putting the mixed raw materials into a ball mill, adding water, a suspending agent, and a dissolving agent, and ball milling to obtain a copper red glaze slurry;

[0036] S3) applying a layer of base glaze on the body, and then applying a layer of copper red glaze slurry and polishing glaze in sequence, and drying;

[0037] S4) sending the dried brick into a kiln for firing, and obtaining glazed Zhonglang red jade tiles after polishing.

[0038] In some examples of the preparation method, the firing temperature is 1150-1235°C.

[0039] In some examples of the preparation method, the firing time is 40 to 70 minutes.

[0040] In some examples of the preparation method, the firing temperature is 1150-1235° C., and the firing time is 40-70 min.

[0041] In some examples of the preparation method, the glaze is selected from at least one of high temperature, low temperature, bright, matte and dry granular glaze.

[0042] The beneficial effects of the present invention are:

[0043] The copper red glaze of the present invention effectively protects the copper alloy particles by using a low-temperature protective glaze of a specific composition, so that the ceramic tiles can be fired under conventional firing conditions (non-reducing atmosphere) to obtain ceramic tiles with bright colors, breaking the limitation of the prior art that a reducing atmosphere is generally required to obtain the copper red glaze. At the same time, the copper red glaze of the present invention can be fired under relatively wide conditions, and the yield rate is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figures 1 to 4 These are photographs of the tiles obtained by firing Examples 1 to 4, respectively.

[0045] Figures 5 to 9 The following are photographs of the tiles obtained by firing in Comparative Examples 1 to 5. DETAILED DESCRIPTION

[0046] The first aspect of the present invention provides:

[0047] A copper red glaze with wide firing conditions is composed of low-temperature protective glaze, copper-aluminum alloy particles, and protective copper alloy particles. The protective copper alloy is a copper alloy other than copper-aluminum alloy. The initial melting temperature of the low-temperature protective glaze does not exceed 1050°C. The chemical mass composition of the low-temperature protective glaze is: Al2O3: 6.02-11.21%, SiO2: 55.22-65.15%, Fe2O3: 0-0.5%, CaO: 10-13.5%, MgO: 0-0.5%, K2O: 4-7%, Na2O: 1-3%, TiO2: 0-0.2%, ZrO2: 0-0.35%, BaO: 2-3.5%, ZnO: 6-13%, B2O3: 0-2% and unavoidable impurities.

[0048] Fe2O3, MgO, TiO2, ZrO2, and B2O3 mainly come from impurities in the raw materials and generally do not require deliberate adjustment.

[0049] Research has shown that this chemical composition of low-temperature protective glaze can protect copper alloys well, allowing the copper alloys to develop colors, and the resulting copper red color is bright and full. Under the combined effect of low-temperature protective glaze and protective copper alloy, the copper-aluminum alloy particles can be guaranteed to develop colors stably.

[0050] In some examples of copper red glaze, the copper-aluminum alloy particles have at least one of the following characteristics:

[0051] 1) The amount of the copper-aluminum alloy particles is 0.2-20% of the dry weight of the low-temperature protective glaze; the amount of copper alloy particles added can be adjusted according to the color development. Specifically, if the overall copper-red surface of the tile is large, the amount can be slightly larger; otherwise, the amount can be slightly smaller. Excessive addition will cause the overall color to be darker or deviate from the design.

[0052] 2) The copper content of the copper-aluminum alloy is 80-99%;

[0053] 3) The particle size of the copper-aluminum alloy particles is 100-500 meshes.

[0054] In some examples of copper red glaze, the protective copper alloy particles have at least one of the following characteristics:

[0055] 1) The protective copper alloy is selected from at least one of bronze powder, brass powder and copper-tungsten powder; these alloys can better avoid the generation of copper black and are more conducive to obtaining a pure and atmospheric copper red effect.

[0056] 2) The total copper content of the protective copper alloy is 85-99%, preferably 85-95%, 85-90%. When the copper content in the copper alloy is insufficient, the copper content can be increased by adding an appropriate amount of copper powder. A high copper content can make more full use of the alloy.

[0057] 3) The amount of the protective copper alloy particles is 0.2-5% of the dry weight of the low-temperature protective glaze and is lower than the amount of the copper-aluminum alloy particles; the amount of the protective copper alloy particles can be adjusted according to the specific color development conditions to achieve a more outstanding copper red glaze.

[0058] 4) The particle size of the protective copper alloy particles is 100 to 500 meshes.

[0059] In some examples of copper red glaze, the particle size of the copper alloy particles is 100-500 meshes, which is conducive to preparing the glaze slurry and facilitating uniform glazing.

[0060] The second aspect of the present invention provides:

[0061] A Zhonglang glaze red jade tile has a glaze layer formed by the copper red glaze described in the first aspect of the present invention.

[0062] In some examples of glazed Zhonglang red jade tiles, it includes a body layer, a base glaze layer, a copper red glaze layer and a polishing glaze layer.

[0063] The glaze layer is preferably a transparent glaze, especially a colorless transparent glaze, which can better show the copper red effect.

[0064] In some examples of glazed Zhonglang red jade tiles, the thickness of the copper red glaze layer is 0.5-0.8 mm.

[0065] In some examples of glaze Zhonglang red jade tiles, the thickness of the glaze layer is 0.2-0.5 mm.

[0066] In some examples of glaze Zhonglang red jade tiles, the thickness of the copper red glaze layer is 0.5-0.8 mm, and the thickness of the polished glaze layer is 0.2-0.5 mm.

[0067] The third aspect of the present invention provides:

[0068] A method for preparing a copper-red glaze ceramic tile, wherein the composition of the copper-red glaze is as described in the first aspect of the present invention, comprising the following steps:

[0069] S1) preparing materials according to the composition of copper red glaze raw materials and mixing the raw materials uniformly;

[0070] S2) putting the mixed raw materials into a ball mill, adding water, a suspending agent, and a dissolving agent, and ball milling to obtain a copper red glaze slurry;

[0071] S3) applying a layer of base glaze on the body, and then applying a layer of copper red glaze slurry and polishing glaze in sequence, and drying;

[0072] S4) sending the dried brick into a kiln for firing, and obtaining glazed Zhonglang red jade tiles after polishing.

[0073] In some examples of the preparation method, the firing temperature is 1150-1235°C.

[0074] In some examples of the preparation method, the firing time is 40 to 70 minutes.

[0075] In some examples of the preparation method, the firing temperature is 1150-1235° C., and the firing time is 40-70 min.

[0076] In some examples of the preparation method, the glaze is selected from at least one of high temperature, low temperature, bright, matte and dry granular glaze.

[0077] The technical solution of the present invention is further explained below in conjunction with examples.

[0078] In the following examples, unless otherwise specified, the exemplary method for preparing ceramic tiles includes the following operations:

[0079] S1) preparing the raw materials according to the components and the quality of each component, and mixing the raw materials uniformly;

[0080] S2) putting the mixed raw materials into a ball mill, adding 30-50% by weight of water, 0.1-0.3% of sodium carboxymethyl cellulose, and 0.2-0.5% of sodium tripolyphosphate, and ball milling for 20-30 minutes to obtain a glaze slurry;

[0081] S3) applying a layer of surface glaze on the brick, then applying a layer of Langhong glaze, and finally applying a layer of polished glaze on the Langhong glaze, and putting it into an oven to dry the moisture;

[0082] S4) sending the dried brick into a kiln for firing at a temperature of 1180-1235° C. for 40-70 min, and obtaining the glazed Zhonglang red jade brick after cooling down.

[0083] The raw materials of low-temperature protective glaze mainly include feldspar, quartz, calcite, calcined kaolin, barium carbonate, zinc oxide, potassium nitrate, potassium carbonate, boric acid or borax, and zirconium silicate.

[0084] The chemical mass compositions of Examples 1 to 4 are shown in Table 1, and the chemical mass compositions of Comparative Examples 1 to 4 are shown in Table 2. In Tables 1 and 2, the values ​​are all in mass percentage, and the amount of copper alloy particles is the percentage of the dry weight of the low-temperature protective glaze.

[0085] Table 1

[0086] Example 1 Example 2 Example 3 Example 4 <![CDATA[Al2O3]]> 7.06 11.47 8.11 6.65 <![CDATA[SiO2]]> 58.07 58.04 62.3 57.15 <![CDATA[Fe2O3]]> 0.12 0.11 0.01 0.05 CaO 12.38 10.33 12.24 11.56 MgO 0.26 1 0.02 0.3 <![CDATA[K2O]]> 7.64 4.2 8 5.78 <![CDATA[Na2O]]> 0.22 2 0.01 0.25 <![CDATA[TiO2]]> 0.05 0.03 0 0.05 <![CDATA[ZrO2]]> 0.29 0.21 0.03 0.33 BaO 2.49 3.03 3.15 3.45 ZnO 11.22 6 13.13 12.99 <![CDATA[B2O3]]> 0 1.2 0.5 2 Copper aluminum alloy powder dosage 0.5 5 10 20 Amount of copper alloy powder for protection 0.5 2 3 5 Types of protective copper alloy powder Copper tungsten powder + copper Brass + Copper Bronze + Copper bronze Total copper content of protective copper alloy 85 92 95 90

[0087] Table 2

[0088] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 <![CDATA[Al2O3]]> 6.07 5.89 7.31 6.81 6.65 <![CDATA[SiO2]]> 68.05 64.69 69.81 69.73 57.15 <![CDATA[Fe2O3]]> / 0.24 0.1 0.09 0.05 CaO 0.38 18 5.24 5.62 11.56 MgO 0.11 2 1.56 1.8 0.3 <![CDATA[K2O]]> 2 2.2 4.1 4 5.78 <![CDATA[Na2O]]> 4 0.6 3.2 2 0.25 <![CDATA[TiO2]]> 0.05 / / / 0.05 <![CDATA[ZrO2]]> / / / / 0.33 BaO 10 / 7.8 7 3.45 ZnO / 5.2 0.8 2 12.99 <![CDATA[B2O3]]> 9 0.01 / / 2 Copper aluminum alloy powder dosage 0.5 5 10 20 20 Amount of copper alloy powder for protection 0.5 2 3 5 —— Types of protective copper alloy powder Copper tungsten powder + copper Brass + Copper Bronze + Copper bronze —— Total copper content of protective copper alloy 85 92 95 90 ——

[0089] In Table 1 and Table 2, the values ​​are all in mass percentage, and the amount of copper alloy particles used is the percentage of the dry weight of the low-temperature protective glaze. The particle size of the copper alloy powder is 100-500 mesh. The copper content of the bronze powder used is 80-90%, the copper content of the brass powder is 85-90%, and the copper content of the copper tungsten powder is 20-30%.

[0090] Example 1

[0091] Process flow: blank → inkjet design → copper red glaze → full polishing glaze → firing → full polishing

[0092] The glaze thickness of copper red glaze is 0.8mm, and the glaze thickness of transparent polished glaze is 0.3mm. The smelting temperature is 1150-1180℃ for 70 min.

[0093] Fired tile samples such as Figure 1 As shown, it can be seen that the glaze surface is smooth and the copper red glaze effect is obvious.

[0094] Example 2

[0095] Process flow: blank → inkjet design → copper red glaze → full polishing glaze → firing → full polishing

[0096] The glaze thickness of copper red glaze is 0.7mm, and the glaze thickness of transparent polished glaze is 0.4mm. It is refined at 1170-1200℃ for 60 min.

[0097] Fired tile samples such as Figure 2 As shown, it can be seen that the glaze surface is smooth and the copper red glaze effect is obvious.

[0098] Example 3

[0099] Process flow: blank → inkjet design → copper red glaze → full polishing glaze → firing → full polishing

[0100] The glaze thickness of copper red glaze is 0.6mm, and the glaze thickness of transparent polished glaze is 0.2mm. The smelting temperature is 1190-1215℃ for 50 min.

[0101] Fired tile samples such as Figure 3 As shown, it can be seen that the glaze surface is smooth and the copper red glaze effect is obvious.

[0102] Example 4

[0103] Process flow: blank → inkjet design → copper red glaze → full polishing glaze → firing → full polishing

[0104] The glaze thickness of copper red glaze is 0.5mm, and the glaze thickness of transparent polished glaze is 0.5mm. The smelting temperature is 1205-1235℃ for 40 min.

[0105] Fired tile samples such as Figure 4 As shown, it can be seen that the glaze surface is smooth and the copper red glaze effect is obvious.

[0106] Comparative Example 1

[0107] Process flow: blank → inkjet design → copper red glaze → full polishing glaze → firing → full polishing

[0108] The glaze thickness of copper red glaze is 0.8mm, and the glaze thickness of transparent polished glaze is 0.3mm. The smelting temperature is 1150-1180℃ for 70 min.

[0109] Fired tile samples such as Figure 5 As shown, the glaze is light brownish yellow with black spots, and there is no copper red glaze effect.

[0110] Comparative Example 2

[0111] Process flow: blank → inkjet design → copper red glaze → full polishing glaze → firing → full polishing

[0112] The glaze thickness of copper red glaze is 0.7mm, and the glaze thickness of transparent polished glaze is 0.4mm. It is refined at 1170-1200℃ for 60 min.

[0113] Fired tile samples such as Figure 6 As shown. The glaze is light grey with black spots on the glaze, and there is no copper red glaze effect.

[0114] Comparative Example 3

[0115] Process: body → inkjet design → copper red glaze → full glaze spray → firing → full polishing

[0116] The glaze thickness of copper red glaze is 0.6mm, and the glaze thickness of transparent polished glaze is 0.2mm. The smelting temperature is 1190-1215℃ for 50 min.

[0117] Fired tile samples such as Figure 7 As shown. The glaze is purple, with brown and black spots and particles, and no copper red glaze effect.

[0118] Comparative Example 4

[0119] Process flow: blank → inkjet design → copper red glaze → full polishing glaze → firing → full polishing

[0120] The glaze thickness of copper red glaze is 0.5mm, and the glaze thickness of transparent polished glaze is 0.5mm. The smelting temperature is 1205-1235℃ for 40 min.

[0121] Fired tile samples such as Figure 8 The glaze is dark brown with obvious black spots and no copper red glaze effect.

[0122] Comparative Example 5

[0123] Process flow: blank → inkjet design → copper red glaze → full polishing glaze → firing → full polishing

[0124] The glaze thickness of copper red glaze is 0.5mm, and the glaze thickness of transparent polished glaze is 0.5mm. The smelting temperature is 1205-1235℃ for 40 min.

[0125] Fired tile samples such as Fig. 9 shown.

[0126] From the above examples, it can be seen that the protective glaze and the protective copper alloy have unexpected effects on the display of copper red. The main difference between Examples 1 to 4 and Comparative Examples 1 to 4 is that the composition of the low-temperature protective glaze is different. Due to the change in the composition of the low-temperature protective glaze, the copper red glaze effect cannot be obtained. The difference between Example 4 and Comparative Example 5 is whether the protective copper alloy is used or not. Comparative Example 5 lacks the protective copper alloy, resulting in a black product color.

[0127] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A copper red glaze with wide firing conditions, characterized in that: The invention is composed of a low-temperature protective glaze, copper-aluminum alloy particles, and protective copper alloy particles. The protective copper alloy is a copper alloy other than copper-aluminum alloy. The initial melting temperature of the low-temperature protective glaze does not exceed 1050°C. The chemical mass composition of the low-temperature protective glaze is: Al2O3: 6.02-11.21%, SiO2: 55.22-65.15%, Fe2O3: 0-0.5%, CaO: 10-13.5%, MgO: 0-0.5%, K2O: 4-7%, Na 2O: 1-3%, TiO2: 0-0.2%, ZrO2: 0-0.35%, BaO: 2-3.5%, ZnO: 6-13%, B2O3: 0-2% and unavoidable impurities; or the raw material mass composition of the low-temperature protective glaze is: feldspar: 30-40 parts, quartz: 18-30 parts, calcite: 10-25 parts, calcined kaolin: 5-10 parts, barium carbonate: 0-5 parts, zinc oxide: 5-15 parts, potassium nitrate: 0-5 parts, potassium carbonate 1-6 parts; The protective copper alloy particles are selected from at least one of bronze powder, brass powder and copper-tungsten powder. The total copper content in the protective copper alloy particles is 85-99%, and the percentage is mass percentage. The amount of the protective copper alloy particles is 0.2-5% of the dry weight of the low-temperature protective glaze and is lower than the amount of the copper-aluminum alloy particles.

2. The copper red glaze according to claim 1, characterized in that: The copper-aluminum alloy particles have at least one of the following characteristics: The amount of the copper-aluminum alloy particles is 0.2-20% of the dry weight of the low-temperature protective glaze; The copper content of the copper-aluminum alloy is 80-99%, and the percentage is mass percentage; The copper-aluminum alloy particles have a particle size of 100 to 500 meshes.

3. The copper red glaze according to claim 1, characterized in that: The particle size of the protective copper alloy particles is 100-500 meshes.

4. The copper red glaze according to any one of claims 1 to 3, characterized in that: The amount of the protective copper alloy particles is 0.2 to 0.5 times the amount of the copper-aluminum alloy particles.

5. A glazed Zhonglang red jade tile, characterized in that: The invention has a glaze layer formed by the copper red glaze according to any one of claims 1 to 4.

6. The Zhonglang red jade tile according to claim 5 is characterized in that: It includes a body layer, a base glaze layer, a copper red glaze layer and a polishing glaze layer.

7. The Zhonglang red jade tile according to claim 6 is characterized in that: The thickness of the copper red glaze layer is 0.5-0.8 mm; and / or the thickness of the polished glaze layer is 0.2-0.5 mm.

8. A method for preparing a copper red glaze ceramic tile, wherein the composition of the copper red glaze is as described in any one of claims 1 to 4, comprising the following steps: S1) preparing materials according to the composition of copper red glaze raw materials and mixing the raw materials uniformly; S2) putting the mixed raw materials into a ball mill, adding water, a suspending agent, and a dissolving agent, and ball milling to obtain a copper red glaze slurry; S3) applying a layer of base glaze on the body, and then applying a layer of copper red glaze slurry and polishing glaze in sequence, and drying; S4) sending the dried brick into a kiln for firing, and obtaining glazed Zhonglang red jade tiles after polishing.

9. The preparation method according to claim 8, characterized in that: The firing temperature is 1150-1235°C and / or the firing time is 40-70 min.

10. The preparation method according to claim 8 or 9, characterized in that: The glaze polishing is selected from at least one of high temperature, low temperature, bright, matte and dry particle glaze polishing.

Citation Information

Patent Citations

  • Method for firing imitativejun porcelaincopper-red glaze under oxidizing atmosphere condition

    CN106746655A

  • Ceramic glazed tile with gold metal effect and preparation method thereof

    CN101880178A

  • Copper red glaze formula and manufacturing process of copper red glaze porcelain

    CN104150965A